Research on Localized Marketing and Business Management Strategies of Chinese New Energy Vehicle Enterprises: A Case Study Based on NIO - Qi, Jie (Transactions on Social Science, Education and Humanities Research, 2024)
With the improvement of environmental awareness and technological progress, new energy vehicles are gradually entering people’s vision. Domestic new energy vehicle brands are emerging one after another, and the willingness of Chinese consumers to purchase new energy vehicles is also constantly increasing. In recent years, NIO has been at the forefront of new energy vehicles in China. This article applies the 4Ps and SWOT analysis to study the marketing strategies of NIO. This study collects information about NIO, organizes and analyzes the collected data. Identify the advantages and existing problems of NIO through these methods and provide corresponding suggestions. Research has found that NIO has a unique marketing strategy. But in recent years, new energy vehicle brands have been constantly emerging, and the problems that have arisen in NIO’s own development have also led to NIO being threatened. Therefore, it is necessary to develop different solutions for different problems and improve the brand image of NIO. NIO’s exposure can be increased through a combination of online and offline methods.